Victimology in Indonesian Criminal Law: An Analysis of the Protection of Victims of Sexual Violence Crimes - Syifatul Zuhra; Muhammad Ryandi Perdana Suandi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the protection of victims of sexual violence crimes from a victimology perspective within Indonesian criminal law. This research employs a normative legal method with a qualitative approach, utilizing statutory and conceptual approaches. Data were collected through library research based on legislation and recent scientific journals published between 2021 and 2026. The results indicate that, normatively, Indonesia has established a relatively strong legal framework, particularly with the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes. However, its implementation remains constrained by several challenges, including limited capacity of law enforcement officials, weak inter-institutional coordination, and structural and cultural factors such as patriarchal culture and victim blaming practices. Furthermore, victims are still at risk of experiencing revictimization during the criminal justice process. From a victimology perspective, this condition reflects that the Indonesian criminal justice system is still in a transitional phase toward victim-oriented justice. Therefore, strengthening the victimological approach through comprehensive legal reform, enhancing the professionalism of law enforcement officers, and transforming legal culture in society are essential to ensure effective and substantive justice for victims.